Economic, legal, and institutional perspectives (Washington, DC)
This book is one of the first comprehensive attempts to look at the synergies between climate change and trade objectives from economic, legal, and institutional perspectives. It addresses an important policy question - how changes in trade policies and international cooperation on trade policies can help address global environmental spillovers, especially GHG emissions, and what the (potential) effects of (national) environmental policies that are aimed at global environmental problems might be for trade and investment. It explores opportunities for aligning development and energy policies in such a way that they could stimulate production, trade, and investment in cleaner technology options.
Keywords: International trade,Thương mại quốc tế